The mechanism for body propulsion in swimming - Barthels, K. M. (Swimming III. Proceedings of the Third International Symposium of Biomechanics in Swimming, University of Alberta, Edmonton, Canada, 1979)
This paper offers a qualitative model of the swimming mechanism that is the result of an attempt to piece together, into a meaningful whole, the isolated bits of information currently at our disposaL Within this modest proposal is an attempt to provide a logical rationale for the desirability of generating maximum forward lift force and minimum forward drag force on the body segments as the most efficient combination to be used for propelling the body.